PENGGUNAAN METODE PENEMUAN UNTUK MENINGKATKAN KETUNTASAN BELAJAR SISWA MATA PELAJARAN MATEMATIKA PADA KONSEP PENJUMLAHAN KELAS II SEMESTER I SD NEGERI 08 TANJUNG ALAM (JURNAL MANAJEMEN PENDIDIKAN, 2019)
The purpose of mathematics lessons at school illustrates that learning is not only in the cognitive field but extends to the psychomotor and affective fields. To realize the objectives of the mathematics lesson, appropriate strategies and learning methods are needed. The discovery method is one of the student-centered methods. Based on the results of research and discussion starting from Before Cycle I to Cycle II, it can be concluded that using the discovery method can improve the ability to add numbers in mathematics. Learning outcomes increased especially in the first cycle of class I meetings with an average of only 73.55 with 55% completeness, but in the first cycle the second meeting increased by an average of 81.02 with a 65% completeness. the class average increased by 84.3 with 75% completeness, until the second cycle II meeting. Average far increased to 87 with 95% completeness, in the second cycle meeting II there was only 1 student who was incomplete. The use of discovery methods can enhance student creativity because using the discovery method makes it possible to develop active student learning.